The development of sympathy from 5 to 7 years: increase, decline or stability? A longitudinal study - Kienbaum, Jutta (Frontiers in Psychology, 2014)
In the present study the development of sympathy in a group of 85 children (43 girls) was investigated over a 3-year period, starting with the last year of child care, when the children were 5 years-old. Sympathy was measured via different measures: two standardized observations, where the children were observed as they witnessed the distress of a puppet in two different situations; two follow-up interviews with the children immediately after the observations; a self-report questionnaire and two other-report questionnaires by parents and teachers. At all three periods the observations and the children’s self-reports (interviews, questionnaire) were intercorrelated. The teachers’ and the parents’ reports were not significantly correlated with any of the other measures at time 1. At times 2 and 3, a few low but significant correlations emerged. As a consequence, the other reports were dropped from further analyses and a composed sympathy measure consisting of observations and self-reports was created. Rank-order stability of this composed measure over the course of the 3 years proved to be high; suggesting that interindividual differences maintained stability. Mean-level differences showed a significant increase over the course of the study with the highest increase in the initial 2 years. Neither gender nor the interaction between gender and time were significant. In conclusion, the measurement of sympathy has proven valid for the childrens’ observations and self-reports. To the question of age-correlated development, stability in sympathy is firstly high and secondly sympathy increases mainly during the time between the last year in child care and the first year in elementary school.